Motor learning as young gymnast's talent indicator - Di Cagno, A.; Battaglia, C.; Fiorilli, G.; Piazza, M.; Giombini, A.; Fagnani, F.; Borrione, P.; Calcagno, G.; Pigozzi, F. (Journal of Sports Science & Medicine, 2014)
Talent identification plans are designed to select young athletes with the ability to achieve future success in sports. The aim of the study was to verify the predictive value of coordination and precision in skill acquisition during motor learning, as indicators of talent. One hundred gymnasts, both cadets (aged 11.5 ± 0.5 yr.) and juniors (aged 13.3 ± 0.5 years), competing at the national level, were enrolled in the study. The assessment of motor coordination involved three tests of the validated Hirtz`s battery (1985), and motor skill learning involved four technical tests, specific of rhythmic gymnastics. All the tests were correlated with ranking and performance scores reached by each gymnast in the 2011, 2012, and 2013 National Championships. Coordination tests were significantly correlated to 2013 Championships scores (p < 0.01) and ranking (p < 0.05) of elite cadet athletes. Precision, in skill acquisition test results, was positively and significantly associated with scores in 2013 (adj. R2 = 0.26, p < 0.01). Gymnasts with the best results in coordination and motor learning tests went on to achieve better competition results in three- year time.Talent identification plans are designed to select young athletes with the ability to achieve future success in sports.